2018
DOI: 10.1007/s10201-018-0548-0
|View full text |Cite
|
Sign up to set email alerts
|

The reaction distance of a planktivorous fish (Scardinius erythrophthalmus) and the evasiveness of its prey (Daphnia pulex × pulicaria) under different artificial light spectra

Abstract: Artificial light at night may affect mortality risk in prey from visually oriented predators because the effect of the artificial light spectrum may differ for a predator's visual prey detection and for prey evasiveness. To test this, we conducted two types of experiment. First, we assessed the reaction distance and swimming speed of juvenile rudd (Scardinius erythrophthalmus) allowed to forage on juvenile Daphnia pulex × pulicaria under three artificial light sources: halogen, high pressure sodium (HPS), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
2
19
0
2
Order By: Relevance
“…Experiments to assess the light‐spectral‐ and light‐intensity‐dependent visual field volume of the fish (i.e., experiments to determine the parameters for the model) revealed another quite interesting results, that is, the reaction distance (as a behavioral proxy for visual prey detection) and swimming speed of planktivorous fish depend not only on light intensity but also on its spectral composition. Our results showed that the reaction distance and swimming speed of juvenile rudd were greater in halogen and metal‐halide lights than in high pressure sodium light, which is consistent with the results of our earlier study (Tałanda et al 2018). The similar effect of different light sources on reaction distance and swimming speed is consistent with the results obtained in earlier studies, in which the greater swimming speed of fish correlated with better visual conditions (e.g., higher light intensity), which was attributed to better visibility and greater foraging activity (Utne‐Palm 1999).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Experiments to assess the light‐spectral‐ and light‐intensity‐dependent visual field volume of the fish (i.e., experiments to determine the parameters for the model) revealed another quite interesting results, that is, the reaction distance (as a behavioral proxy for visual prey detection) and swimming speed of planktivorous fish depend not only on light intensity but also on its spectral composition. Our results showed that the reaction distance and swimming speed of juvenile rudd were greater in halogen and metal‐halide lights than in high pressure sodium light, which is consistent with the results of our earlier study (Tałanda et al 2018). The similar effect of different light sources on reaction distance and swimming speed is consistent with the results obtained in earlier studies, in which the greater swimming speed of fish correlated with better visual conditions (e.g., higher light intensity), which was attributed to better visibility and greater foraging activity (Utne‐Palm 1999).…”
Section: Discussionsupporting
confidence: 93%
“…In conclusion, the results of our study confirmed the suggestions presented in the earlier studies that changes in light intensity due to the presence of artificial light at night may force Daphnia to select greater depths in the water column, which results in a decrease in their individual growth rates and, in turn, decreases their fitness (Moore et al 2006, Tałanda et al 2018). Moreover, the results also suggest that another feature of artificial light, that is the specificity of its spectral characteristics (which largely differs from the spectral characteristics of natural light), may affect the fitness of Daphnia individuals, since Daphnia in the experiments were not able to correctly assess the spectrum‐dependent mortality risk due to predation by fish in the vertical gradient of several artificial light sources (i.e., halogen and metal halide lamps).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All these factors are species‐specific and light intensity‐dependent (Batty, ; Tian, Zhang, Xu, Wang, & Liu, ). Light intensity enables fish to see diets for feeding (Boeuf & Le Bail, ; Elliott, ), escape from predators (James & Heck, ; Tałanda, Maszczyk, & Babkiewicz, ), hunt suitable preys (Cerri, ; Granqvist & Mattila, ) and find out habitats (Harvey, Butler, McLean, & Shand, ; Mol & Ouboter, ). Light can also influence the skin colour of some fishes which may be changed by the absorption, reflection and scattering of light by the pigments and microstructures within the fish integument (Leclercq, Taylor, & Migaud, ; Sugimoto, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that negative phototaxisis together with being smaller at first reproduction are fish anti-predator defence Daphnia mechanisms, and that these defences are more effective under low light intensities of 37-153 lux (Effertz and von Elert, 2014;Effertz and von Elert, 2017). At higher light intensities, fish predation efficiencies towards Daphnia preys are high and hence anti-predatory defences are less effective (Tałanda et al, 2018). This means that in the present study the higher reported effects at low than at high light intensity agree with reported cost-benefits of anti-predatory defences.…”
Section: Discussionmentioning
confidence: 99%